Ethan learns to be a learning organization. Issue 6 (5th August 2014) - Rana, Geeta; Goel, Alok
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to describe the main human resource management policies at Ethan Power Private Ltd, an Indian design, sales and manufacturing company, and the specific circumstances that led it to become a learning organization. Design/methodology/approach – This paper outlines the company's origins and growth and its policies in such areas as recruitment, induction, training, remuneration, performance management and industrial relations. Findings – This paper reveals that learning organization concepts have stimulated debate in the business, and there is growing acceptance of self-managed development, empowerment and creativity. Practical implications – This paper explains that there is much more evidence in the company of effective teamwork and the principles of total quality management, while HR specialists are encouraging the processes of reflection and self-improvement that lie at the heart of organizational improvement. Social implications – This paper reveals that, in general, and while fully complying with industrial-relations legislation, the company prefers to employ people who are not members of a trade union. Originality/value – This paper details the factors that led an Indian organization to change its organizational culture and how this change was achieved.